DENSITOMETRIC METHOD FOR ASSESSING BONE TISSUE DENSITY IN ANTERIOR MAXILLA WITH PROGNOSTIC PURPOSE - H.I. Krynychnyh; S.M. Shuvalov; V.S. Pavlov; O.V. Kulytska; V.V. Nahaichuk; M.L. Muntian (Український стоматологічний альманах)
Density studies, or the densitometric method, are used in the maxillofacial area to monitor the treatment course and to improve or correct, when necessary, the treatment plan for the number of dento-facial diseases or conditions.